2021
DOI: 10.1097/hn9.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the criteria for a difficult intubation alert in the age of videolaryngoscopy: a scenario-based, multidisciplinary, multi-institutional provider survey

Abstract: Introduction: Our goal was to characterize further variability in how providers both define a difficult intubation and apply a difficult tracheal intubation alert. Materiala and Methods: We developed a survey describing 26 different intubation scenarios encompassing a range of clinical complexity and equipment. Scenarios included multiple factors hypothesized to impact a provider’s definition of a difficult intubation and the threshold for a difficult i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although a large proportion of our difficult airway cohort were successfully managed with VL, our staff still issued a difficult airway alert. In contrast, the more recent study by Allyn et al8 reported that difficult DL rescued by VL would not warrant a difficult airway alert in the majority of providers at their centers. Our study period dated back to 2011–2016 and failed DL may no longer be as worrisome for airway providers because of increasing familiarity with VL devices, widespread availability of the devices, and an expanding scope of daily usage.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Although a large proportion of our difficult airway cohort were successfully managed with VL, our staff still issued a difficult airway alert. In contrast, the more recent study by Allyn et al8 reported that difficult DL rescued by VL would not warrant a difficult airway alert in the majority of providers at their centers. Our study period dated back to 2011–2016 and failed DL may no longer be as worrisome for airway providers because of increasing familiarity with VL devices, widespread availability of the devices, and an expanding scope of daily usage.…”
Section: Discussionmentioning
confidence: 87%
“…The criterion constituting a "difficult airway" to a boardcertified staff anesthesiologist who performs airway management regularly, may be different from other clinicians [8] with less experience, support, and access to advanced airway tools. Previous survey-based studies [8,15] have employed prefabricated scenarios with various combinations of airway management modalities and graded degrees of difficulty to determine the threshold for a difficult airway alert. Whereas, in our observational study the determinants for assigning a difficult airway alert were derived from real scenarios encountered by our staff.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations